2020
DOI: 10.2298/jsc190917122d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-desorption behaviour of clomazone in Regosol and Chernozem agricultural soils

Abstract: Studies of adsorption and desorption of pesticides by soils are important for understanding and predicting their fate and transmission in the environment. Considering the agricultural and environmental relevance of clomazone, its sorption-desorption behaviour was studied in two widespread Serbian agricultural soil types named Regosol and Chernozem. Both phenomena are well-described by the Freundlich equation, which shows that clomazone is generally sorbed more to organic matter than to the mineral soil fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…It has been reported that clomazone’s sorption to the soil depends more on the OM content than the soil particles (clay or sand) (Gunasekara et al 2009). However, it has also been reported that a higher clay fraction increases clomazone’s soil sorption (Đurović-Pejčev et al 2020; Li et al 2004; Loux et al 1989). For instance, Đurović-Pejčev et al (2020) reported that clomazone sorption in two soils with similar organic carbon (Regosol: 1.15% and Chernozem: 1.93%), was greater in the soil that had a higher clay content (Regosol: 23.4% and Chernozem: 28.9%); the Chernozem.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that clomazone’s sorption to the soil depends more on the OM content than the soil particles (clay or sand) (Gunasekara et al 2009). However, it has also been reported that a higher clay fraction increases clomazone’s soil sorption (Đurović-Pejčev et al 2020; Li et al 2004; Loux et al 1989). For instance, Đurović-Pejčev et al (2020) reported that clomazone sorption in two soils with similar organic carbon (Regosol: 1.15% and Chernozem: 1.93%), was greater in the soil that had a higher clay content (Regosol: 23.4% and Chernozem: 28.9%); the Chernozem.…”
Section: Resultsmentioning
confidence: 99%
“…The Freundlich parameter ( K f ) and the Langmuir parameter ( C s(0) ) demonstrated the significantly greater sorption in the organically modified montmorillonites. If we compare the K f values for clomazone sorption on HDTMA-montmorillonites and PTMA-montmorillonites with those for clomazone sorption in natural soils, organically modified montmorillonites displayed greater sorption capacity (Đurović-Pejčev et al ., 2020). Moreover, greater sorption occurred in HDTMA-montmorillonites than in PTMA-montmorillonites.…”
Section: Resultsmentioning
confidence: 99%
“…), cotton ( Gossypium hirsutum L. ), corn ( Zea mays L. ), etc. (Liebl & Norman, 1991; Culpepper et al ., 2001; TenBrook & Tjeerdema, 2006; Đurović-Pejčev et al, 2020). The effectiveness of clomazone is based on its inhibition of carotenoid pigment synthesis, which protects chlorophyll and other plant constituents from photodegradation (Duke et al ., 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine whether and to what extent clomazone concentrations affect its sorption kinetic behavior, the lowest and highest initial concentration previously used in clomazone sorption experiments were included in the study. 19 Short-term sorption kinetics parameters were obtained by applying the hyperbolic, pseudo-first- and pseudo-second-order models, 20 while the Elovich equation, intraparticle diffusion and two-site nonequilibrium models were used to examine the sorption mechanisms and potential rate-controlling stage. 9,15,21…”
Section: Introductionmentioning
confidence: 99%